MEREMEDIASI MISKONSEPSI SISWA TENTANG PERPINDAHAN KALOR MENGGUNAKAN CLIS BERBANTUAN ANIMASI SWISH MAX - Sismawati, Sismawati; Djudin, Tomo; Arsyid, Syaiful B. (Universitas Tanjungpura, 2023)
This research study aimed to investigate the effectiveness of the Cooperative Learning Integrated with SWiSH Max (CLIS) animation model in remedying misconceptions among seventh-grade students at MTs Muhammadiyah Sejangkung. The research followed a pre